Conductas disruptivas y su incidencia en el entorno escolar - Cedeño Macías, Adriana Adelaida (2020)
The present research comprises a quite common problem in homes and schools, which is disruptive behavior, this case, is about the incidence of these in the school environment, taking into account the case of a 7 year old girl who suffers from this problem. This issue is of great importance for psychologists, family members, teachers, and classmates, who are part of the institution in which the girl is working. A clinical case of a 7-year-old girl who was diagnosed with a behavioural disorder of an infantile origin is presented. She was brought by her mother to the CIPEM (Centro Integral de Promoción y Empleo de la Mujer), where the pre-professional practices were carried out. The most predominant symptoms that maintained this disorder were known, through the application of diverse psychological techniques in the interviews that were held.